High-thermal-conductivity uvioresistant composite fabric and preparation method thereof
By connecting functional nanoparticles with a core-shell structure formed on the fiber surface with a silk fibroin network, the problems of decreased breathability and easy shedding of functional fillers in existing technologies are solved, resulting in a composite fabric with high thermal conductivity and UV resistance, while maintaining comfort and durability.
Patent Information
- Application Number
- CN202610270585.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-06
- Publication Date
- 2026-05-15
AI Technical Summary
Existing textiles primarily achieve their thermal conductivity or UV protection through surface covering, which leads to reduced breathability, easy shedding of functional fillers, insufficient durability, and damage to fibers during high-temperature treatment. It is difficult to achieve a balance between high thermal conductivity, UV protection, and wearing comfort.
Functional nanoparticles with a core-shell structure are formed on the fiber surface and combined with hydroxylated boron nitride nanosheets through spontaneous oxidative polymerization of dopamine hydrochloride. By utilizing silk fibroin to form a three-dimensional interconnected network, a stable connection with thermal conductivity and UV resistance is achieved.
A high thermal conductivity and UV-resistant composite fabric was prepared, which maintains breathability and soft feel, improves functionality and durability, is suitable for heat-sensitive fibers, has fixed chemical bonds with no risk of leaching, and is safe in the preparation process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional fabric technology, specifically to a high thermal conductivity and UV-resistant composite fabric and its preparation method. Background Technology
[0002] With people's increasing demands for outdoor activities, occupational protection, and wearing comfort, functional textiles that combine efficient thermal management and excellent UV protection have become an important research and development direction for fabrics. The focus is on developing textiles that can retain their inherent flexibility, breathability, and wearing comfort to the greatest extent while having stable thermal conductivity and UV resistance.
[0003] Currently, the thermal conductivity or UV protection functions of textiles are mainly achieved through finishing processes, namely, constructing functional coatings or films on the fabric surface, primarily through processes such as coating, padding, spraying, and composite pressing. These technologies typically disperse functional fillers in polymer resin to form a finishing slurry, which is then fixed onto the fabric surface. However, functional fabrics prepared through surface coating have the following drawbacks: First, to form a continuous and dense functional layer to ensure performance, a high coating coverage and thickness are often required, which can clog fabric pores, leading to decreased breathability and moisture permeability, and a stiffer hand feel. Second, the interfacial bonding between physically blended functional fillers and the polymer resin matrix is weak. After repeated washing and rubbing, the fillers are prone to detachment or migration, resulting in rapid functional degradation and insufficient durability. Third, many functional fillers are difficult to disperse uniformly in polymer resin, easily agglomerating, forming thermal resistance points and affecting the uniformity of the coating. In addition, traditional processes require high-temperature heat treatment or high-energy radiation to achieve resin curing and cross-linking, which is not only energy-intensive but also damages heat-sensitive fibers.
[0004] To overcome some of the aforementioned shortcomings, those skilled in the art have modified the surface of fillers to improve dispersibility or developed cross-linked UV absorbers to improve washability. However, most of these improvements focus on the material formulation level and fail to fundamentally change the "dense surface coating" approach. Therefore, it has always been difficult to achieve a breakthrough in balancing functional durability and wearing comfort.
[0005] Therefore, there is an urgent need for a composite fabric that can be made lightweight and breathable while also having high thermal conductivity and UV resistance, free from the dependence on thick coatings. Summary of the Invention
[0006] Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a high thermal conductivity and UV-resistant composite fabric and its preparation method. Thermally conductive nanoparticles and UV-resistant units are firmly and uniformly fixed on the surface of each fiber, and a stable link is formed at the fiber intersection through chemical cross-linking, constructing a three-dimensional, continuous, stable and durable functional network, thus solving the problems mentioned in the background technology.
[0007] Technical solution To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a method for preparing a high thermal conductivity and UV-resistant composite fabric is provided, comprising the following steps: S1. Dopamine hydrochloride and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone were polymerized with hydroxylated boron nitride nanosheets in Tris-HCl buffer to obtain a dispersion. S2. The fabric substrate is placed in an ethanol solution containing 3-aminopropyltriethoxysilane for activation treatment to obtain activated fabric; S3. First, the activated fabric is immersed in the dispersion solution and then pressed. Then, it is immersed in the silk fibroin solution for a second time and pressed again to obtain a wet fabric. S4. The wet fabric is treated with water vapor, dried, and shaped to obtain the thermally conductive and UV-resistant composite fabric.
[0008] This invention first involves the simultaneous polymerization of hydroxylated boron nitride nanosheets and 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone molecules in a room-temperature aqueous solution via the spontaneous oxidation polymerization of dopamine and the interfacial adsorption effect. 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone is covalently bonded to the polydopamine network, forming a stable shell on the surface of the hydroxylated boron nitride nanosheets. The polydopamine on the shell surface then anchors the nanosheets to the surface of each fiber. Finally, silk fibroin is used to form molecular welds at the fiber intersections, constructing a three-dimensional biomimetic functional network isomorphic to the textile network. Thermal conductivity and UV protection are rapidly transferred along the fiber skeleton, while the porosity between fibers is completely preserved. This achieves both high thermal conductivity and UV protection while ensuring the fabric's comfort and breathability.
[0009] Preferably, in step S1, the mass ratio of the hydroxylated boron nitride nanosheets to dopamine hydrochloride and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone is 1:2~3:0.5~1.
[0010] More preferably, in step S1, the mass ratio of the hydroxylated boron nitride nanosheets to dopamine hydrochloride and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone is 1:2:0.75.
[0011] Preferably, in step S1, the thickness of the hydroxylated boron nitride nanosheets is less than 5 nm.
[0012] Preferably, the polymerization reaction is carried out under nitrogen atmosphere with magnetic stirring at room temperature for 12-24 hours.
[0013] Preferably, in step S2, the concentration of 3-aminopropyltriethoxysilane in the ethanol solution containing 3-aminopropyltriethoxysilane is 1-3%.
[0014] In this application, by activating the fabric, amino groups are introduced onto the fiber surface, which significantly enhances the chemical bonding force between the fabric and polydopamine.
[0015] Preferably, in step S2, the activation treatment temperature is 40~60℃ and the time is 1~3h.
[0016] Preferably, in step S3, the soaking time for one soaking is 30-50 minutes; The second immersion time is 15-25 minutes.
[0017] Preferably, in step S4, the temperature of the steam treatment is 50~60℃, the relative humidity is ≥95%, and the time is 4~6h.
[0018] Preferably, in step S4, the drying temperature is 80~100℃ and the time is 30~60min; The shaping temperature is 120~130℃, and the time is 2~3 minutes.
[0019] According to a second aspect of the present invention, a high thermal conductivity and UV-resistant composite fabric obtained according to the above preparation method is provided, having an in-plane thermal diffusivity of 25~35 mm. 2 / s, UV protection factor UPF > 50. Beneficial effects
[0020] This invention provides a high thermal conductivity and UV-resistant composite fabric and its preparation method. It has the following beneficial effects: This solution provides a method for preparing a high thermal conductivity and UV-resistant composite fabric. First, the spontaneous oxidative polymerization of dopamine hydrochloride is used to combine 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone to form a stable shell structure on the surface of hydroxylated boron nitride nanosheets, thereby preparing functional nanoparticles with a core-shell structure. Then, polydopamine is bonded to the fabric through an impregnation process. Finally, water vapor induces silk fibroin to transform from a hydrophilic random coil structure into a stable gel network rich in hydrophobic β-sheet crystals, locking and encapsulating the functional nanoparticles on the surface of the fabric fibers, thus preserving the porous structure of the fabric. At the same time, the film mainly coats the surface of individual fibers, preserving excellent comfort and breathability.
[0021] This solution provides a method for preparing a high thermal conductivity and UV-resistant composite fabric. All preparation methods are carried out in an aqueous phase, and the reaction conditions are mild, making it suitable for the preparation of various fabrics, especially heat-sensitive fibers.
[0022] This solution provides a high thermal conductivity and UV protection composite fabric with excellent thermal conductivity and UV protection coefficient. At the same time, because the fabric's pore structure is preserved, the original breathability of the fabric is not reduced. In addition, since the film mainly covers single fibers, the bending stiffness of the fabric increases by less than 20%, which has no impact on the feel. The abrasion fastness reaches level 4 or above.
[0023] This solution provides a high thermal conductivity and UV-resistant composite fabric. The functional nanoparticles are fixed by chemical bonds, eliminating the risk of dissolution. Furthermore, the entire preparation process is carried out in an aqueous phase without organic solvents, making it safer for the human body. Detailed Implementation
[0024] The present invention will be further described in detail below with reference to the embodiments. However, the implementation of the present invention is not limited thereto. Various substitutions and modifications can be made based on ordinary technical knowledge and conventional means in the art without departing from the above-described technical concept of the present invention, and all such substitutions and modifications should be included within the scope of the present invention.
[0025] The hydroxylated boron nitride nanosheets in this invention are prepared by the following method: Boron nitride nanosheets were dispersed in a 10 mol / L sodium hydroxide solution and stirred at 120 °C for 3 h. After filtration, the solution was repeatedly washed with deionized water until the pH of the filtrate was 7. Then, the solution was dried at 50 °C for 8 h to obtain hydroxylated boron nitride nanosheets.
[0026] The technical solution of the present invention will be described in detail below with reference to specific embodiments. Example
[0027] Step 1: 200 mg of hydroxylated silicon nitride nanosheets with a sheet thickness of 3 nm were dispersed in 1 L of Tris-HCl buffer and sonicated for 2 h. Then, 400 mg of dopamine hydrochloride and 150 mg of 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone were added and magnetically stirred at room temperature under a nitrogen atmosphere for 24 h to allow dopamine to polymerize simultaneously on the surface of hydroxylated silicon nitride nanosheets and 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone molecules. 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone was covalently bonded to the polydopamine network to form a stable shell. After the reaction was completed, the product was collected by centrifugation and washed three times with water to fully disperse it in water, resulting in a black stable dispersion with a concentration of 5 mg / mL. Step 2: The polyester fabric is ultrasonically cleaned for 15 minutes each in acetone, ethanol and deionized water to remove spinning oil. The cleaned polyester fabric is then placed in an ethanol solution containing 1 wt% 3-aminopropyltriethoxysilane and treated at 50°C for 1 hour to introduce amino groups onto the surface of the polyester fibers. After removing the polyester fabric, it is rinsed with ethanol and then dried at 80°C to obtain activated polyester fabric. Step 3: Place the activated polyester fabric in the dispersion and let it stand at room temperature for 30 minutes to allow the functional nanoparticles to be fully adsorbed onto the fiber surface. After taking it out, roll it with a pressure of 0.3 MPa through a padding machine to remove excess liquid. Then immerse the fabric in the silk fibroin solution and soak it again for 20 minutes. Roll it again to ensure that the wet fabric is evenly loaded. Step 4: Hang the wet fabric in a constant temperature and humidity chamber with a humidity of 96% and a temperature of 50℃ for 5 hours. After the treatment, dry it with a forced air at 80℃ for 30 minutes. Finally, heat set the fabric at 120℃ for 2 minutes to obtain a high thermal conductivity and UV resistant composite fabric. Example
[0028] Step 1: 150 mg of hydroxylated silicon nitride nanosheets with a sheet thickness of 2 nm were dispersed in 1 L of Tris-HCl buffer and sonicated for 2 h. Then, 375 mg of dopamine hydrochloride and 100 mg of 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone were added and magnetically stirred for 18 h at room temperature under a nitrogen atmosphere to allow dopamine to polymerize simultaneously on the surface of hydroxylated silicon nitride nanosheets and 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone molecules. 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone was covalently bonded to the polydopamine network to form a stable shell. After the reaction was completed, the product was collected by centrifugation and washed three times with water to fully disperse it in water, resulting in a black stable dispersion with a concentration of 5 mg / mL. Step 2: The cotton fabric is ultrasonically cleaned for 15 minutes each in acetone, ethanol and deionized water to remove spinning oil. The cleaned cotton fabric is then placed in an ethanol solution containing 2 wt% 3-aminopropyltriethoxysilane and treated at 45°C for 2 hours to introduce amino groups onto the surface of the polyester fibers. After removing the cotton fabric, it is rinsed with ethanol and then dried at 80°C to obtain activated cotton fabric. Step 3: Place the activated cotton fabric in the dispersion and let it stand at room temperature for 30 minutes to allow the functional nanoparticles to be fully adsorbed onto the fiber surface. After taking it out, roll it with a pressure of 0.3 MPa through a padding machine to remove excess liquid. Then immerse the fabric in the silk fibroin solution and soak it again for 20 minutes. Roll it again to ensure that the wet fabric is evenly loaded. Step 4: Hang the wet fabric in a constant temperature and humidity chamber with a humidity of 96% and a temperature of 55℃ for 5 hours. After the treatment, dry it with a forced air at 80℃ for 30 minutes. Finally, heat set the fabric at 120℃ for 2 minutes to obtain a high thermal conductivity and UV resistant composite fabric. Example
[0029] Step 1: 250 mg of hydroxylated silicon nitride nanosheets with a sheet thickness of 4 nm were dispersed in 1 L of Tris-HCl buffer and sonicated for 2 h. Then, 625 mg of dopamine hydrochloride and 175 mg of 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone were added and the mixture was magnetically stirred at room temperature under a nitrogen atmosphere for 24 h to allow dopamine to polymerize simultaneously on the surface of the hydroxylated silicon nitride nanosheets and 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone molecules. 2-hydroxy-4-(3-methacryloxypropoxy)benzophenone was covalently bonded to the polydopamine network to form a stable shell. After the reaction was completed, the product was collected by centrifugation and washed three times with water to fully disperse it in water, resulting in a black stable dispersion with a concentration of 5 mg / mL. Step 2: The polyester fabric is ultrasonically cleaned for 15 minutes each in acetone, ethanol and deionized water to remove spinning oil. The cleaned polyester fabric is then immersed in an ethanol solution containing 1.5 wt% 3-aminopropyltriethoxysilane and treated at 50°C for 1 hour to introduce amino groups onto the surface of the polyester fibers. After removing the polyester fabric, it is rinsed with ethanol and then dried at 80°C to obtain activated polyester fabric. Step 3: Place the activated polyester fabric in the dispersion and let it stand at room temperature for 30 minutes to allow the functional nanoparticles to be fully adsorbed onto the fiber surface. After taking it out, roll it with a pressure of 0.3 MPa through a padding machine to remove excess liquid. Then immerse the fabric in the silk fibroin solution and soak it again for 20 minutes. Roll it again to ensure that the wet fabric is evenly loaded. Step 4: Hang the wet fabric in a constant temperature and humidity chamber with a humidity of 96% and a temperature of 58℃ for 5 hours. After the treatment, dry it with a forced air at 80℃ for 30 minutes. Finally, heat set the fabric at 120℃ for 2 minutes to obtain a high thermal conductivity and UV resistant composite fabric.
[0030] Comparative Example 1 Step 1: 200 mg of unmodified boron nitride nanosheets and 150 mg of 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone were directly ultrasonically dispersed in 100 g of aqueous polyurethane emulsion to form a finishing slurry. Step 2: The polyester fabric is ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each to remove the spinning oil. The finishing sizing agent is then applied to the cleaned polyester fabric surface by scraping to form a coating with a thickness of 0.5 mm. The coating is then dried and cured at 120°C for 10 minutes to obtain the composite fabric.
[0031] Comparative Example 2 Step 1: Disperse 200 mg of hydroxylated silicon nitride nanosheets with a sheet thickness of 3 nm in 1 L of Tris-HCl buffer and sonicate for 2 h. Then add 150 mg of 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone and stir magnetically for 24 h at room temperature under nitrogen atmosphere. After sonication, centrifuge to collect the product and wash it three times with water. Disperse it fully in water to obtain a black stable dispersion with a concentration of 5 mg / mL. Step 2: The polyester fabric is ultrasonically cleaned for 15 minutes each in acetone, ethanol and deionized water to remove spinning oil. The cleaned polyester fabric is then placed in an ethanol solution containing 1 wt% 3-aminopropyltriethoxysilane and treated at 50°C for 1 hour to introduce amino groups onto the surface of the polyester fibers. After removing the polyester fabric, it is rinsed with ethanol and then dried at 80°C to obtain activated polyester fabric. Step 3: Place the activated polyester fabric in the dispersion and let it stand at room temperature for 30 minutes to allow the functional nanoparticles to be fully adsorbed onto the fiber surface. After taking it out, roll it with a pressure of 0.3 MPa through a padding machine to remove excess liquid. Then immerse the fabric in the silk fibroin solution and soak it again for 20 minutes. Roll it again to ensure that the wet fabric is evenly loaded. Step 4: Hang the wet fabric in a constant temperature and humidity chamber with a humidity of 96% and a temperature of 50℃ for 5 hours. After the treatment, dry it with a forced air at 80℃ for 30 minutes. Finally, heat set the fabric at 120℃ for 2 minutes to obtain a high thermal conductivity and UV resistant composite fabric.
[0032] Comparative Example 3 The preparation method of this comparative example is the same as that of Example 1. The difference is that in step 4, constant temperature and humidity steam treatment is not performed. Instead, the fabric is directly dried at 80°C for 30 minutes and finally heat-set at 120°C for 2 minutes.
[0033] The thermally conductive and UV-resistant composite fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests, and the test results are shown in Table 1.
[0034] Table 1
[0035]
[0036] According to the data in Table 1, firstly, core-shell structured functional nanoparticles are prepared and then combined with silk fibroin to achieve fiber-level network connection. Polydopamine ensures that the ultrathin BNNS (thickness <5nm) is highly oriented and densely arranged on the fiber surface, and forms effective connections at fiber intersections. The β-fold network of silk fibroin (SF) further fixes and bridges these thermally conductive units, thereby constructing an ultra-efficient biomimetic leaf vein-like three-dimensional thermally conductive network with high thermal conductivity and UV resistance, while the fabric is soft and breathable.
[0037] Comparative Example 1 shows the preparation of composite functional fabrics using the traditional method of coating and curing the fabric surface to form a film. BNNS undergoes disordered agglomeration in the water-based polyurethane emulsion, and the thick coating leads to a significant reduction in air permeability.
[0038] In Comparative Example 2, the omission of dopamine hydrochloride resulted in a decrease in the adhesion strength at the interface, which also led to uneven adhesion of BNNS and easy detachment, making it impossible to form a continuous pathway. This significantly reduced thermal conductivity and also significantly reduced the retention rate of friction resistance and UV resistance coefficients.
[0039] In Comparative Example 3, no water vapor treatment was performed, resulting in the purification of silk fibroin, which led to a loosening of the functional network, a significant reduction in heat transfer efficiency, and a significant decrease in the retention rate of abrasion resistance and UV resistance coefficients.
[0040] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high thermal conductivity and UV-resistant composite fabric, characterized in that: Includes the following steps: S1. Dopamine hydrochloride and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone were polymerized with hydroxylated boron nitride nanosheets in Tris-HCl buffer to obtain a dispersion. S2. The fabric substrate is placed in an ethanol solution containing 3-aminopropyltriethoxysilane for activation treatment to obtain activated fabric; S3. First, the activated fabric is immersed in the dispersion solution and then pressed. Then, it is immersed in the silk fibroin solution for a second time and pressed again to obtain a wet fabric. S4. The wet fabric is treated with water vapor, dried, and shaped to obtain the thermally conductive and UV-resistant composite fabric.
2. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S1, the mass ratio of the hydroxylated boron nitride nanosheets to dopamine hydrochloride and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone is 1:2~3:0.5~1.
3. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S1, the thickness of the hydroxylated boron nitride nanosheets is less than 5 nm.
4. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: The polymerization reaction was carried out under nitrogen atmosphere with magnetic stirring at room temperature for 12-24 hours.
5. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S2, the concentration of 3-aminopropyltriethoxysilane in the ethanol solution containing 3-aminopropyltriethoxysilane is 1-3%.
6. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S2, the activation treatment is performed at a temperature of 40~60℃ for 1~3 hours.
7. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S3, the soaking time for each soaking is 30-50 minutes; The second immersion time is 15-25 minutes.
8. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S4, the temperature of the steam treatment is 50~60℃, the relative humidity is ≥95%, and the time is 4~6h.
9. The method for preparing a high thermal conductivity and UV-resistant composite fabric according to claim 1, characterized in that: In step S4, the drying temperature is 80~100℃ and the time is 30~60min; The shaping temperature is 120~130℃, and the time is 2~3 minutes.
10. The high thermal conductivity and UV-resistant composite fabric obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The in-plane thermal diffusivity is 25~35mm. 2 / s, UV protection factor UPF > 50.